Peran Orang Tua dalam Pertumbuhan Balita pada Masa Pandemi Covid-19 - Ni Nyoman Ayu Desy Sekarini; Putu Irma Pratiwi; Luh Nik Armini (Universitas Ngudi waluyo, 2022)
During the Covid-19 pandemic, it had an impact on the health, economy and tourism sectors. During this pandemic, it is also estimated that the number of poverty rates will increase to 12.4%. This also indirectly affects the fulfillment of nutrition, especially toddlers, so it is estimated that there will be an increase in cases of undernourished children under five, which is 15%, which means that there will also be an increase in stunting cases. In the context of preventing and controlling malnutrition and stunting during the COVID-19 pandemic, it requires the participation of families, especially parents of toddlers as the frontline in family health. The purpose of this study was to determine the relationship between the role of parents and the growth of toddlers (0-59 months) during the Covid-19 pandemic. The type of research is quantitative research with analytic design and cross-sectional approach. The sample used is toddlers aged 0-59 months in the Sukasada Strait Village, Buleleng, with a total of 108 respondents and using a sampling technique that is simple random sampling. Data collection is done directly by giving a questionnaire on the role of parents in the growth of toddlers. Furthermore, measurements of height/length and weight of toddlers were carried out. The type of data used is primary data with ordinal scale and the data is analyzed univariate and bevariate. The results of the analysis showed that under five with good nutrition 88 (81.5%), excess nutrition 10 (9.3%), undernutrition 6 (5.6%) and malnutrition 4 (3.7%). Toddlers with a normal height of 91 (84.3%), toddlers with stunting 14 (13%), several stunted 2 (1.9) and height 1 (0.9%). The statistical test results obtained that there was a relationship between the role of parents and the nutritional status of toddlers (p value = 0.025) and there was a relationship between the role of parents and stunting status in toddlers (p value = 0.047). Involving parents is very important in efforts to prevent and treat wasting and stunting in toddlers Abstrak Pada masa pandemi Covid-19 menimbulkan dampak pada sektor kesehatan, perekonomian dan pariwisata. Pada masa pandemic ini juga diperkirakan jumlah angka kemiskinan meningkat menjadi 12,4%. Hal ini juga secara tidak langsung berpengaruh pada pemenuhan gizi khususnya balita, sehingga diperkirakan terjadi peningkatan kasus balita kurang gizi yaitu 15%, yang artinya juga terjadi peningkatan kasus stunting. Dalam rangka pencegahan dan pengendalian kurang gizi dan stunting pada masa pandemic covid-19, memerlukan peran serta keluarga khususnya orang tua balita sebagai garda terdepan dalam kesehatan keluarga. Tujuan penelitian ini adalah mengetahui hubungan peran orang tua dengan pertumbuhan balita (0-59 bulan) pada masa pandemi Covid-19. Jenis penelitian yaitu penelitian kuantitatif dengan rancangan analitik dan pendekatan crossectional. Sampel yang digunakan yaitu balita usia 0-59 bulan di Desa Selat Sukasada Buleleng sejumlah 108 responden dan menggunakan teknik pengambilan sampel yaitu simple random sampling. Pengumpulan data dilakukan secara langsung dengan memberikan kuisioner peran orang tua dalam pertumbuhan balita. Selanjutnya dilakukan pengukuran tinggi/panjang badan serta berat badan balita. Jenis data yang digunakan yaitu data primer dengan skala ordinal dan data dianalisis univariat dan bivariat. Hasil analisis diperoleh balita dengan gizi baik 88 (81,5%), gizi berlebih 10 (9,3%), gizi kurang 6 (5,6%) dan gizi buruk 4 (3,7%). Balita yang memiliki tinggi badan normal 91 (84,3%), balita dengan stunting 14 (13%), several stunted 2 (1,9) dan tinggi 1 (0,9%). Hasil uji statistik diperoleh terdapat hubungan peran orang tua dengan status gizi balita (p-value = 0,025) serta terdapat hubungan antara peran orang tua dengans status stunting pada balita (p-value = 0,047). Melibatkan orang tua merupakan hal yang sangat penting dalam upaya pencegahan dan penanganan wasting dan stunting pada balita.